Implementation of Mutlaqah Mudharabah Agreement on Hajj Savings Products at Bank Syariah Indonesia KCP Gunung Tua - Rizki Munaito Siregar; Ahmad Perdana Indra; Tuti Anggraini (Yayasan Riset dan Pengembangan Intelektual, 2024)
Hajj is one of the pillars of Islam that must be believed and carried out by every Muslim who has fulfilled the mandatory requirements which will perfect the fifth pillar of Islam. The Hajj pilgrimage is actually an obligation for Muslims. Bank Syariah Indonesia Gunung Tua Sub-Branch Office is one of the sharia financial institutions that provides services for the Hajj pilgrimage using a system that can make it easier for customers, namely Hajj savings. This savings aims to make it easier for prospective Hajj pilgrims by setting aside some of their money so they can pay for expenses. pilgrimage trip. This research uses field research, with qualitative research methods to explore data through interviews, observation and data analysis. The research results obtained are that the implementation of the mutlaqah mudharabah agreement on the Hajj savings of Bank Syariah Indonesia KCP Gunung Tua is in accordance with sharia and the terms of the mudharabah contract. And the system used by Bank Syariah Indonesia KCP Gunung Tua is revenue sharing, meaning that the Indonesian bank as mudharib and the customer as shahibul mall receive a profit share from the bank's total income. Bank Syariah Indonesia has been very helpful, making it very easy for customers to be able to fulfill their wish of getting a Haj portion number and continuing on to the holy land.